2017
DOI: 10.1038/srep44727
|View full text |Cite
|
Sign up to set email alerts
|

The immune correlates of protection for an avian influenza H5N1 vaccine in the ferret model using oil-in-water adjuvants

Abstract: Because of the pathogenicity and low incidence of avian influenza virus infections in humans, the immune correlates of protection for avian influenza vaccines cannot be determined from clinical studies. Here, we used the ferret model to address this for an avian influenza H5N1 vaccine. Using oil-in-water adjuvants, we generated groups of ferrets with undetectable (geometric mean titer [GMT] < 10), low (GMT = 28.3), or high (GMT > 761.1) hemagglutination-inhibition (HAI) titers to the A/Viet Nam/1203/2004 (H5N1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
(49 reference statements)
1
18
0
Order By: Relevance
“…We have since shown that although neutralizing (HAI and MN) antibodies are the best immune correlate for protection, non-neutralizing antibodies can still reduce disease severity. 46 Hence, despite the possibility of vaccine degradation, this batch of stockpiled vaccine can still afford protection, especially when administered with adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…We have since shown that although neutralizing (HAI and MN) antibodies are the best immune correlate for protection, non-neutralizing antibodies can still reduce disease severity. 46 Hence, despite the possibility of vaccine degradation, this batch of stockpiled vaccine can still afford protection, especially when administered with adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the addition of an adjuvant, the immune response can be weak, especially when compared to the immune response elicited by a live homologous infection [45,46]. The lack of an antibody response is associated with a lack of protection [47]. For instance, naïve ferrets immunized with A(H3N2)/Hong Kong/X31/1968 vaccine were all susceptible to homologous challenge and none produced vaccine-specific serum HAI antibodies [39].…”
Section: Low Vaccine Seroconversion Proportions In Naïve Ferretsmentioning
confidence: 99%
“…Due to this issue, pandemic influenza vaccines can be adjuvanted to ensure an efficient immune response [52][53][54][55]. With the inclusion of different adjuvants, different magnitudes of seroconversion and protection can be achieved [47]. Some studies used virus-like particle (VLP) vaccines produced from insect cells using a baculoviral system which results in 100% seroconversion [56,57].…”
Section: Low Vaccine Seroconversion Proportions In Naïve Ferretsmentioning
confidence: 99%
“…Although the development of broadly neutralizing antibody responses against influenza remains a critical goal, emerging evidence suggests that extra-neutralizing antibody functions also play an important role in protection from infection (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Studies with passive transfer of neutralizing monoclonal antibodies in mice have shown that Fcγ receptors are required for protection from lethal infection, via mechanisms that do not block viral entry (18).…”
Section: Introductionmentioning
confidence: 99%